PERSEPSI DUNIA USAHA SALON KECANTIKAN TERHADAP KOMPETENSI PRAKTEK KERJA INDUSTRI SISWA TATA KECANTIKAN SMK NEGERI 7 PADANG - YUPELMI, MIMI; Hayatunnufus, Hayatunnufus; rahmiati, rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research intent describe effort the world perception beauty salon to industrial working practice interest student Sets SMK'S beauty Country 7 Moorlands. This research gets quantitative descriptive character. Total population 46 person and samples as much 30 person with samples taking tech it purposive is sampling one that taken from by pro employee at its area and was working more than 1 year at beauty salon. Data analysis tech utilize percentage formula. Acknowledged observational result perception universalizes beauty salon effort to afektif's interest student industry working practice Sets SMKN'S beauty 7 Moorland lies on pretty good category with percentage 90,1%. Meanwhile effort the world perception beauty salon to psikomotor's interest student industry working practice Sets SMKN'S beauty 7 Moorland lies on good category with percentage 88,8%. Of descriptive analysis result gets to be seen that efforts world perception beauty salon to industrial working practice interest student Set SMKN'S beauty 7 Moorland lies on pretty good category with percentage 89,45%.